Evaluating the efficacy of Atriplex spp. in the phytoextraction of road salt (NaCl) from contaminated soil. (October 2020) - Mann, Ellen; Rutter, Allison; Zeeb, Barbara
Abstract: Soil and freshwater salinization are growing issues worldwide. Road salt, primarily sodium chloride (NaCl), is a significant contributor to this issue in North America. In this study, the ability of three native Canadian halophytes ( Atriplex patula, Atriplex hortensis, and Atriplex canescans ) to remove Na + and Cl − from contaminated soil was investigated. Field and greenhouse studies determined plant survivability in roadside areas, as well as Na + and Cl − extraction levels. The Atriplex spp. accumulated 18–55 mg Na + g −1 dry weight (DW) and 41–64 mg Cl − g −1 DW when grown for a two-month period in soil spiked with NaCl to simulate a very highly contaminated roadside. Using A. patula, it would theoretically take 6 growing seasons to remove all salt from an area contaminated with 1540 μg Cl − g −1, while A. hortensis and A. canescens would take 19 and 9 years, respectively. Salt content in shoot components (seeds, stem, leaves) was determined to provide further insight on phytoextraction processes. In all three Atriplex species, the leaves had the highest Cl − concentration, followed by the seeds (bracteoles included), with the lowest concentrations found in the stem. These novel findings provide important information for road salt remediation and indicate that using Atriplex spp. may be a viable way in which to reduce the environmental impact of road salting. Graphical abstract: Image 1 Highlights: Phytoextraction of road salt from roadside soil is a viable remediation method. Phytoremediation of salinized soil applied to road salt impacted soil. Demonstrates a novel method of managing emerging soil and freshwater salinization. Abstract : Summary: This article demonstrates that Canadian halophytes can remediate road-salt impacted soil in less than 10 years.